Prevalence and course of depression in older people with aortic stenosis undergoing transcatheter aortic valve implantation – a systematic review and meta-analysis - Maschke, Verena; Mons, Ute; Lohner, Valerie (BMC geriatrics, 2025)
Background Depression is the most prevalent psychiatric disorder in older people with cardiovascular disease and an independent risk factor for cardiac surgery outcomes. Given the rising number of older people with aortic stenosis in need of transcatheter aortic valve implantation (TAVI) and the increasingly recognized role of depression as a prognostic factor, this systematic review and meta-analysis aimed to derive a global estimate of the prevalence of depression and to examine its course from pre- to post-TAVI. Methods We included articles reporting prevalence of depression (diagnosed or assessed using validated instruments) or change in depressive symptoms in people undergoing TAVI. We performed three main meta-analyses: (1) prevalence of diagnosed depression, (2) prevalence of assessed depression and (3) standardized mean change (SMC) of depressive symptoms from pre- to post-TAVI. Results We included 32 studies in this systematic review, 26 of which were suitable for meta-analysis. The pooled prevalence of diagnosed and assessed depression was 6.0% [95%-Confidence interval: 3.3, 10.6] and 18.5% [13.0, 25.6], respectively. We observed a small, albeit non-significant trend towards a decrease in depressive symptoms from pre- to post-TAVI (SMC: -0.08 [-0.37, 0.22]). Conclusions A relevant proportion of people undergoing TAVI experiences depression, and the discrepancy in prevalence estimates of diagnosed and assessed depression indicates a potential under-diagnosis of depression. Disease management strategies should be adapted to include screening for and adequate treatment of depression in this population. Improvement of depressive symptoms after TAVI should not be taken for granted.